2001
DOI: 10.3349/ymj.2001.42.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings of Metastatic Disease to the Thyroid

Abstract: The goal of this study was to evaluate the sonographic findings of thyroid metastases arising from non-thyroid primaries. The study over a 5-year period comprised nine patients who had histopathologically proven metastatic disease to the thyroid. Ultrasonography was available in all cases. Ultrasound-guided needle aspiration was performed on 10 suspected nodules as determined by ultrasound. The Ultrasonographic findings were analyzed in two different ways. The first analysis included only those nodules biopsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 0 publications
6
40
0
1
Order By: Relevance
“…In the literature the typical ultrasound image of secondary tumours is not specified. The most commonly reported are heterogeneous, hypoechoic lesions with blurred margins, often with calcifications [23] or without them [30]. In our material metastatic tumours presented calcifications twice as often as benign lesions, while primary tumours showed calcifications three times more often than benign lesions.…”
Section: Prace Oryginalnementioning
confidence: 67%
See 1 more Smart Citation
“…In the literature the typical ultrasound image of secondary tumours is not specified. The most commonly reported are heterogeneous, hypoechoic lesions with blurred margins, often with calcifications [23] or without them [30]. In our material metastatic tumours presented calcifications twice as often as benign lesions, while primary tumours showed calcifications three times more often than benign lesions.…”
Section: Prace Oryginalnementioning
confidence: 67%
“…Early diagnosis including a thyroid FNA result allows the avoidance of unnecessary thyroid surgery in some cases. On the other hand, when analysis is mainly based on biopsy results, the limitation is a frequent impossibility to distinguish primary, especially non-differentiated, thyroid cancers from secondary tumours [11,14,[23][24][25]. In such cases the FNA result indicates only the need to take into account…”
Section: Discussionmentioning
confidence: 99%
“…Our results were opposite against the previous studies, which were focused on only focal lesions on thyroid gland. 5,8) In numerous large cohort autopsy studies, the most common primary non-thyroidal origin of thyroid metastases was lung or breast. 1,[10][11][12] These thyroid metastases detected on autopsy tended to be clinically occult.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In contrast, the incidence of thyroid metastases ranges from 2% to 24% in the patients affected by widespread malignant neoplasm according to autopsy studies. 5) Some investigators have suggested that thyroid metastases were no longer considered rare. Thyroid metastases arising from non-thyroidal malignancies have been reported in 1.4-3% of patients who underwent surgery for thyroid cancer; 2,6,7) however, the actual number of thyroid metastases may be greater because not all patients undergo surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation